Color Storytelling Sebagai Visual Narrative Pada Film Animasi The Red Turtle (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2023)
The Red Turtle is an animated film released in 2016. It was directed by Dutch-British animator Michall Dudok de Wit. The film is a co-production between Wild Bunch and Studio Ghibli. The Red Turtle tells of the struggle of a man stranded on an uninhabited island to survive until he finally finds new happiness on the island. The film "The Red Turtle" lacks dialogue on its storyline, making color the main visual element of the film's narrative. This attracted researchers to study the film The Red Turtle from the color storytelling aspect that played a narrative visual on the development of the story. The purpose of this study to explain color storytelling can play a narrative visual in the film "The Red Turtle". This study used a qualitative descriptive approach. It uses Albert Munsell's color theory studies, with data collection using observations, documentation and Library studies, and with interactive model data analysis techniques. The results of this study show that color visual elements, color storytelling, are as important and as important as narrative, suggesting that color storytelling can play a narrative visual role in the animated film "The Red Turtle".